WATER DEFICIT EVALUATION ON SEED VIABILITY AND VIGOUR OF VARIOUS CHILI VARIETIES (Capsicum annum L.) USING VARIOUS CONCENTRATION OF PEG 6000 IN GERMINATION AND GROWTH PHASE - Panti Ciptaning Kusuma Wardhani; Ami Suryawati; Lagiman Lagiman (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2018)
The research was carried out to find out chili varieties which gave high seed viability and vigour on germination and growth phase in water deficit evaluation using PEG-6000. There were 2 experiments, the first experiment was 4x10 Factorial arranged on Randomized Complete Design with three replicates using petridish. The first factor was PEG-6000 concentration of: 0%, 10%, 15% and 20%. The second factor was chili varieties namedly TM 33 , TM 99, Kastilo , OR Doni 77 , OR Twist 42 , Kaka 99 , OR Twist 22, Red sabel, Rimbun 3, Amro 99. The second experiment was 6x2 Factorial arranged on Randomized Complete Design with four replications using polybag. The first factor was chili varieties which had high viability and vigour on first experiment: TM 33 , Kastilo , OR doni 77, OR twist 22 , Red sabel and Rimbun 3 varieties. The second factor were normal and deficit watering. The data was subjected to an analysis of variance followed by Duncan’s Multiple Range Test and LSD 5%.The results indicated that TM 33, Kastilo, OR twist 22, Red sabel and Rimbun 3 had high viability on germination phase in water deficit evaluation using PEG-6000. TM 33, OR twist 22 and Rimbun 3 had tolerance growth in deficit watering.Keywords: chilli, water deficit, PEG-6000, viability, vigor